The Bleeding Disorders: Current Concepts and Management - Walker, Irwin R. (1988)
Bleeding disorders are relatively uncommon, and most bleeding episodes occur as a result of local factors. Therefore a positive history of bleeding usually does not accurately predict the presence of a bleeding disorder. In a few cases the existence of certain patterns of bleeding, such as hemarthroses and petechiae, does allow an accurate prediction. On the other hand, the absence of bleeding following significant challenge is very helpful indeed in excluding a bleeding disorder. However, a negative history of bleeding in the absence of hemostatic challenge does not exclude a bleeding disorder. Accurate clinical analysis of suspected bleeding disorder requires acquaintance with the common causes of bleeding; these are described along with a clinical approach to diagnosis. The laboratory investigation starts with the performance of the “hemostasis screen”. A normal hemostasis screen excludes by far the majority of acquired defects, and further investigation, other than a repeat of the bleeding time, is rarely needed. When hereditary disorders are suspected, specific assay of individual factors, usually factors VIII (hemophilia A), IX (hemophilia B) and Von Willebrand factor, is advised. Recent advances in the understanding and the management of some disorders are described.